(untitled) (Research, Society and Development, 2019)
Siliceous steels are the ones that contain a percentage of approximately 3% silicon and they are used to manufacture generators, transformers and industrial motors. Through the research, understand their metallurgical properties about electrical steel and also conciliate these properties with processes parameters from this material. A standard sample taken from the batch selected for testing was pickled using hydrochloric acid and subjected to the annealing procedure. Proportional calculations were made using the iron silicon diagram, taking into account the weight and dimensions of the sample. After annealing, the sample was submitted to the appropriate tests to show grain size and its influence on magnetic properties. The results showed significant growth in grain size after secondary annealing and generation of the Goss texture, which is desired for the material. By the analyses was possible conclude that after annealing process, the grain showed standard size, and the magnetic loss and permeability resulted in 1,5 W/Kg and 1,99T respectively at 1,7T induction condition at 60Hz frequency (Brazilian standard frequency).